Advances in light water reactor technologies - Saito, Takehiko (Springer, 2011)
Advances in Light Water Reactor Technologies focuses on the design and analysis of advanced nuclear power reactors. This volume provides readers with thorough descriptions of the general characteristics of various advanced light water reactors currently being developed worldwide. Safety, design, development and maintenance of these reactors is book?s the main focus, with key technologies like full MOX core design, next-generation digital I&C systems and seismic design and evaluation described at length. Also covered are: -Technologies currently being developed and utilized in a number of countries worldwide -A number of new recent developments in light water reactors -Analyses of different types of light water reactors from leading academics working on design and analysis Advances in Light Water Reactor Technologies is the ideal book for researchers and engineers working in nuclear power that are interested in learning the fundamentals of advanced light water plants.